Radial versus femoral access for coronary interventions: An updated systematic review and meta‐analysis of randomized trials. Issue 7 (28th January 2021) - Chiarito, Mauro; Cao, Davide; Nicolas, Johny; Roumeliotis, Anastasios; Power, David; Chandiramani, Rishi; Sartori, Samantha; Camaj, Anton; Goel, Ridhima; Claessen, Bimmer E.; Stefanini, Giulio G.; Mehran, Roxana; et al.
Abstract: Objective: It is still debated if benefits associated with radial versus femoral access for coronary angiography and percutaneous coronary interventions (PCI) are due to the access site selection itself, operator expertise or other underlying mechanisms. Methods: We searched PubMed, Embase, and meeting abstracts for randomized trials comparing radial versus femoral access site for coronary angiography and PCI. Primary safety endpoint was major bleeding. Coprimary efficacy endpoints were stroke and myocardial infarction (MI). This study is registered with PROSPERO. Results: We identified 31 trials (30, 096 patients, PCI performed in 21, 225 patients). Radial compared to femoral access was associated with a significant risk reduction in major bleeding (OR 0.53, 95%CI 0.42–0.66, I 2 = 3.3%). Findings were consistent regardless of clinical characteristics or whether coronary angiography was performed with or without PCI. The benefit of radial access was significantly increased in studies published before 2010 and in patients with chronic coronary syndrome. Risk for stroke (OR 1.11, 95%CI 0.76–1.64, I 2 = 0%) and MI (OR 0.90, 95%CI 0.79–1.04, I 2 = 0%) were comparable between the groups. Risk for mortality and vascular complications were significantly lower with radial than femoral access. Conclusion: In patients undergoing coronary angiography and PCI, radial access is associated with a significant risk reduction in bleeding, vascular complications, and mortality compared to femoral access. The risk of stroke or MI were comparable in patients with radial or femoral access.